Rep. Rashida Tlaib on the Subject of the Right to Clean Water - Pasquini, Phil (The Washington report on Middle East affairs, 2021)
On September 27, a group of youth from the Sunrise Movement held a press conference at the Capitol in support of President Joe Biden's proposed $3.5 trillion budget reconciliation bill, arguing that it is a critical way to invest in human capital while also investing in a sustainable infrastructure. Three progressive representatives, Rashida Tlaib (D-MI), Ro Khanna (D-CA) and Jamaal Bowman (D-NY), lent their support by each speaking briefly about issues raised by the youth activists. Collectively, they pinpointed climate change as an issue that must be at the forefront of the decision-making process. They also warned against following the usual default plan of relying on carbon intensive solutions that enrich corporations at the expense of the environment and ordinary people.